The Use of Organic Fertilizer Enriched with Bacteria to Improve the Fertility of the Soil - Neni Marlina; Rosmiah Rosmiah; Khusnul Khotimah; Helmizuryani Helmizuryani; Berliana Palmasari; Nurbaiti Amir; Joni Phillep Rompas; Dewi Meidelima (Altifani Journal: International Journal of Community Engagement, 2024)
Majority of farmers in Ketapang 1.  Rantau Panjang District  are accustomed to using inorganic chemical fertilizers and a few use organic fertilizers. Excessive use of chemical fertilizers will have a negative effect on soil fertility, physically, chemically and biologically. Infertile soil can cause the soil to become hard and cause plant roots to develop less well and disrupt nutrient absorption, so that the production of all plants will decrease, therefore to increase soil fertility you can use organic fertilizer enriched with Azospirillum bacteria (N-fixing bacteria from air) and phosphate and potassium solubilizing bacteria. This organic fertilizer enriched with bacteria more quickly contributes the NPK nutrients needed by plants. This activity was carried out in Ketapang 1 village, Rantau Panjang District, Ogan Komering Ilir Regency, in the form of counseling and demonstration of the application of organic fertilizer enriched with bacteria. Knowledge about organic fertilizer enriched with bacteria is very beneficial to society to reduce the use of chemical fertilizers, to make the soil more loose and fertile and crop production can increase.